Isotopic Composition of Abiogenic Gas Produced in Closed-System Fischer-Tropsch Synthesis: Implications for the Origins of the Deep Songliao Basin Gases in China - Zhifu Wei; Yongli Wang; Gen Wang; Xueyun Ma; Wei He; Ting Zhang; Xiaoli Yu; Yan-Rong Zou (Geofluids)
In this study, closed-system Fischer-Tropsch synthesis was conducted at 380°C and 30 MPa for 72 h with magnetite as a catalyst. The isotopic composition of the closed-system Fischer-Tropsch synthesis gas and the composition of known abiogenic gas were systematically studied, and the deep Songliao Basin gas was also investigated. The results show that closed-system Fischer-Tropsch synthesis of gaseous hydrocarbon isotopes exhibits a partial reverse order, which includes the reverse order of methane and ethane such as δ13C-C1>δ13C-C2<δ13C-C3 and δ2H-C1>δ2H-C2<δ2H-C3. Furthermore, experimental data on the control of NaBH4 content indicates that the carbon isotopes demonstrate a reverse order on condition that the H2/CO2 (mole ratio) is equal to or greater than 4.0; meanwhile, the hydrogen isotopes show a normal order. The deep Songliao Basin hydrocarbon gas component is similar to thermogenic gas and has a trend of a transition to oceanic hydrothermal system abiogenic gas. In addition, the deep Songliao Basin gas isotopic pattern is different from both Lost City and Kidd Creek where the deep Basin gas carbon isotopic pattern has a reverse order, and the hydrogen isotopic pattern has a normal order. Therefore, the deep Basin gas might be a mixture of the oil-type gas and the coal-formed gas, which could be the cause of the isotopic reverse.